Pim3 up-regulation by YY1 contributes to diabetes-induced cardiac hypertrophy and heart failure - Xiao Jin; Yi Ren; Li Wang; Hao Xie; Lu Huang; Juan Zhang; Zuo-Ying Hu (Iranian Journal of Basic Medical Sciences)
Objective(s): The close relationship of proto-oncogenes to myocardial hypertrophy has long been recognized, and cardiac hypertrophy leads to heart failure (HF). However, whether proviral insertion of Moloney virus 3 kinase (Pim3), a proto-oncogene, contributes to cardiac hypertrophy in diabetes mellitus (DM) remains unknown. This study aims to investigate whether Pim3 is involved in DM-induced cardiac hypertrophy and HF and to elucidate its underlying mechanisms.Materials and Methods: DM was induced in mice by intraperitoneal injection of streptozotocin. Cardiac function was evaluated by echocardiography, and cardiac hypertrophy was determined through histological analysis, quantitative real-time polymerase chain reaction, and western blotting. Silencing RNA transfection and lentivirus-mediated gene knockdown were performed both in vitro and in vivo. Transcriptional activity was analyzed using chromatin immunoprecipitation and luciferase reporter assay.Results: Compared with C57BL/6J mice, cardiac hypertrophy and dysfunction were observed in mice with DM. Pim3 mRNA and protein expression were significantly up-regulated in diabetic hearts and high glucose-cultured H9C2 cells. Yin Yang 1 (YY1), which translocated from the cytoplasm into the nucleus under hyperglycemia, bound to the Pim3 promoter and enhanced Pim3 transcriptional activity. Pim3 or YY1 knockdown profoundly reduced cell size and inhibited the mRNA and protein expression of cardiac hypertrophy markers, as well as markedly attenuating myocardial hypertrophy and cardiac dysfunction.Conclusion: Hyperglycemia induced nuclear translocation of YY1, leading to Pim3 up-regulation, eventually developing into cardiac hypertrophy and HF. Targeting YY1-Pim3 signaling may be a promising therapeutic avenue for DM-induced cardiac hypertrophy and HF.